The Impact of Coping Strategies on Employees' Quality of Life: Work-Life Balance as a Mediator at PT Bank Nagari Lubuk Basung Branch - Faizah, Lodina; Zona, Mega Asri (Human Resource Management Studies, 2024)
First, how coping mechanisms impact quality of life; second, how coping mechanisms impact work-life balance (3) how a healthy work-life balance affects happiness (4) how work-life balance mediates the impact of coping mechanisms on life satisfaction. This study is an example of a causal study. The 46 people who work at the PT Bank Nagari Lubuk Basung Branch made up the study's population. The complete sampling approach was employed to collect samples from 46 workers. Collecting data via the use of a Likert-scale questionnaire. The methodology used in the analysis facilitated by SmartPLS 4. This study's data processing findings show that: (1) PT Bank Nagari Lubuk Basung Branch workers' quality of life is positively and significantly impacted by coping techniques. PT Bank Nagari Lubuk Basung Branch workers' work-life balance is positively and significantly impacted by their coping mechanisms. Thirdly, workers at the PT Bank Nagari Lubuk Basung Branch report higher quality of life when they are able to strike a good work-life balance. Work-life balance is a mediator between coping methods and quality of life for PT Bank Nagari Lubuk Basung Branch workers.